PEREMPUAN DAN POLITIK LOKAL (STUDI KASUS PEMILIHAN KEPALA DAERAH DI SULAWESI TENGGARA) - Hadi Machmud (Institut Agama Islam Negeri Kendari, 2019)
This qualitative study aimed to investigate the existence of women’s contestation in the local election in South East Sulawesi and to identify the female candidates’ effort to win the electoral competition. Data gathered from interview, observation, and documents were analyzed based on the analytical framework used. Findings of the study reveal that the contestation of female regency or major candidates has been of great consideration due to their previous strategic ruling position in the government, such as vice of major, head of the local house of representative, member of the house of regional representative, and local government secretary. Furthermore, the female candidates have a big chance to succeed in the election regarding that they have big force, and their offered programs are beneficial for women and marginal communities. These female candidates also involve more female volunteers’ force who is competent and potential in running activities along with women organization and aiming at empowering women communities.